P020 Evaluating Patient Perspectives on Confidentiality in Sexual Health Clinics. (30th June 2016) - Warren, Sian; Forbes, Georgina; Souter, Emily
Abstract : Background/introduction: Since the introduction of the Venereal Diseases Act in 1917, confidentiality has been a key part of sexual health clinics in the UK. With the repealing of the VD Act, we devised a service evaluation to determine the patient's perspectives on confidentiality. Aim(s)/objectives: To determine patient understanding of the confidentiality process in a large inner city integrated sexual health (ISH) clinic. Methods: A patient questionnaire was designed and given to ISH clinic patients between 18 th of May and 5 th of June 2015. Results: 163 responses were obtained from the ISH clinic (49% female, 51% male). 89% patients reported confidentiality to be important or very important when attending the ISH clinic, with 97% patients reporting confidentiality to be important or very important in the diagnosis of STI's. With regards to ISH offering a non-judgmental service; 95% patients reporting this to be important or very important. 68% patients reported the importance of ISH clinic records being kept separate from GP and hospital records. 45% patients reported they would not attend their GP for STI testing due to a variety of reasons such as embarrassment, convenience and wanting to attend a specialised service. Discussion/conclusion: This study confirms that confidentiality in the diagnosis of STI's and the non-judgemental care that patients receive continues to be important to service users. These factors influence which services patients wish to access for sexual health needs. It is therefore essential that ISH services continue to provide this level of care.